CONFIDENT CARING: AN INNOVATIVE APPROACH TO EDUCATING AND SUPPORTING LAY CARERS OF PATIENTS WITH PALLIATIVE ILLNESS. Issue 1 (1st March 2014) - Swan, S; Shaw, K
Abstract : Introduction: The National Health Service in Glasgow depends on 56, 400 unpaid carers to support and provide care for unwell friends or family. Presently, the majority of deaths are in those aged over 65 and are often following a prolonged period of illness and frailty. This has huge implications on care resources and places increasing responsibility on lay carers. Aim(s) and method(s): The pilot project 'Confident Caring' was developed in an effort to address some of the consequences of this. Two Community Clinical Nurse Specialists researched, designed and delivered a supportive educational programme within the community. Relevant topics were identified through lay and professional consultation and included defining palliative care, caring for the carer, symptom management and end of life care. These were delivered over eight weekly sessions at which an average of eight carers attended. Results: The course was evaluated by written weekly questionnaires and an independently led audio recorded focus group. A validated Carer Support Needs Assessment Tool was administered pre and post course. This global evaluation demonstrated that overall confidence and awareness of the carers was heightened, whilst sharing their experiences with people in a similar situation was beneficial and helped reduce feelings of isolation. Tangible outcomes were identified through the completion of 'Do Not Attempt Cardiopulmonary Resuscitation' forms for two carers and the prescribing of appropriate medications for one carer. Conclusion(s): Providing carer support for the palliative population in this way has shown significant benefits and positive outcomes and further work is planned to validate these encouraging findings.